Implementasi Teori Kognitif Sosial: Dampak Herding Behavior terhadap Peningkatan Penyerapan Anggaran - Martina Wulandari; Supramono Supramono; Andriani Ika Sulistyawati (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
The Ministry of Religious Affairs (MoRA) mandated 70% budget absorption target by July. MoRA's Central Java Province achieved 48–49% in 2022–2023. No prior research whether herding bias moderate the relationship between these structural factors and budget absorption. Study aims: analyze the direct effects of budget planning, budget revisions, and regulations on budget absorption, examine whether herding bias moderates these relationships. Grounded in Bandura's Social Cognitive Theory, about behavior results from interactions between personal, behavioral, and environmental factors. Method: A quantitative, with purposive sampling of 100 respondents. Results: The absence of herding moderation is explained by the dominance of personal factors within SCT. Officers possess high competence, extensive experience and emotional stability, which enable independent decision-making. Conclusion: personal factors can override herding bias in public sector.